2019
DOI: 10.1016/j.ijscr.2019.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of gastric perforation secondary to chicken bone: A report of 2 cases

Abstract: HighlightsThe majority of ingested foreign bodies pass through the gastrointestinal tract harmlessly.Ingested foreign bodies can cause significant complications like bowel obstruction, bleeding, abscess formation, migration to other organs, and perforation.In selected cases, endoscopic management is more cost-effective, minimally invasive, has less post-operative complications, and leads to a more expeditious recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The incidence of intestinal perforation due to foreign body ingestion is less than 1% [2,3]. Sometimes after perforation they can migrate to adjacent organs with the result of fistulization, abscess formation or sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of intestinal perforation due to foreign body ingestion is less than 1% [2,3]. Sometimes after perforation they can migrate to adjacent organs with the result of fistulization, abscess formation or sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these cases occur in children, but also in a considerable number of psychiatric, disabled, or elderly patients with dentures. 80-90% of foreign bodies are spontaneously excreted without repercussions [1], but at least 1% of cases present complications such as gastrointestinal perforations, with the formation of secondary abscesses infrequent [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Sidiqui et al [9] reported two cases of successful endoscopic removal of foreign body from the stomach. On examination both patients were haemodynamically stable with localised epigastric tenderness.…”
Section: Discussionmentioning
confidence: 99%